2015
DOI: 10.15226/2374-6890/2/4/00131
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine and Diabetic Retinopathy: Review of Published Screening Programs

Abstract: Background Diabetic Retinopathy (DR) is a leading cause of blindness worldwide even though successful treatments exist. Improving screening and treatment could avoid many cases of vision loss. However, due to an increasing prevalence of diabetes, traditional in-person screening for DR for every diabetic patient is not feasible. Telemedicine is one viable solution to provide high-quality and efficient screening to large number of diabetic patients. Purpose To provide a narrative review of large DR telemedicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 65 publications
0
12
0
1
Order By: Relevance
“…In a review, Das et al [41] determined that DR is highly suitable for telemedicine because it saves time and minimizes lost income for the patient. DR telescreening can also provide cost savings for health systems depending on the population being screened (see the "Cost-effectiveness of screening" section); for example, a review highlighted that remote and underserved areas benefited most, with one rural teleophthalmology program resulting in savings of $150 per patient over 7 years [42].…”
Section: Telemedicine-based Screeningmentioning
confidence: 99%
“…In a review, Das et al [41] determined that DR is highly suitable for telemedicine because it saves time and minimizes lost income for the patient. DR telescreening can also provide cost savings for health systems depending on the population being screened (see the "Cost-effectiveness of screening" section); for example, a review highlighted that remote and underserved areas benefited most, with one rural teleophthalmology program resulting in savings of $150 per patient over 7 years [42].…”
Section: Telemedicine-based Screeningmentioning
confidence: 99%
“…According to the American Telemedicine Association Validation Level, the first phase of our APDR screening system can be classified as a category 1 program, with an on-disease/non-disease diagnostic criterion issued by the PCP [ 24 ]. Meanwhile, the second phase, characterized by the review of pathological retinographies by the referring ophthalmologist is classified as a category C2 program.…”
Section: Discussionmentioning
confidence: 99%
“…Screening with teleophthalmological means can have a significant impact on reducing vision loss caused by DR. Nationwide-based systems but also community-based programs are proving to boost the screening rates and result in avoiding visual complications around the world [33]. Tozel et al completed a review of large DR telemedicine screening programs for DR across the globe and demonstrated that a high level of clinical accuracy and easier patient access are accomplished [34]. Unnecessary referral minimizing and cost-saving are also reported in recent studies for both rural population and urban community teleophthalmology services [35,36].…”
Section: Retinal Disordersmentioning
confidence: 99%